2022
DOI: 10.3389/fnut.2022.913966
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences at Early Old Stage in Glycolipid Metabolism and Fatty Liver in Offspring Prenatally Exposed to Chinese Great Famine

Abstract: BackgroundAbout 50 years ago, Chinese Great Famine (CGF) affected the entire population in China, and its long-term influence on the offspring has attracted significant attention for research. However, information on possible metabolic differences between sexes is limited. This study explored whether there might be sex differences in the risks of development of glucolipid metabolic dysfunction and fatty liver following prenatal exposure to CGF.Materials and MethodsThere were 11,417 subjects around 55 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A study showed that after exposure to famine in China during the fetal period, there would be 'catch-up growth' after birth, and the risk of glucose and lipid metabolism disorders in the famine-exposed group was significantly higher than that in the non-exposed group. 10 Second, epigenetic modifications (such as DNA methylation) are also a possible influencing mechanism. Many experimental studies have shown that DNA methylation induced by malnutrition in early development can significantly increase the risk of cardiovascular system and metabolic disorders in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that after exposure to famine in China during the fetal period, there would be 'catch-up growth' after birth, and the risk of glucose and lipid metabolism disorders in the famine-exposed group was significantly higher than that in the non-exposed group. 10 Second, epigenetic modifications (such as DNA methylation) are also a possible influencing mechanism. Many experimental studies have shown that DNA methylation induced by malnutrition in early development can significantly increase the risk of cardiovascular system and metabolic disorders in offspring.…”
Section: Discussionmentioning
confidence: 99%